2015
DOI: 10.1051/lhb/20150069
|View full text |Cite
|
Sign up to set email alerts
|

Mise en œuvre de la méthode de cartographie du ruissellement IRIP pour l'analyse des risques lies aux écoulements sur l'infrastructure ferroviaire

Abstract: RÉSUMÉ. -Les voies ferrées sont des éléments structurant des bassins versants qui modifient les chemins de l'eau. Le réseau ferré national est équipé de dispositifs hydrauliques de collecte et d'acheminement des écoulements depuis l'amont de l'infrastructure jusqu'à un exutoire. Le ruissellement est à l'origine de nombreux incidents sur les infrastructures ferroviaires; autant sur les ouvrages linéaires que sur les aménagements connexes nécessaires à l'exploitation ferroviaire. Ces incidents peuvent trouver le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Defrance et al (2014) and Javelle et al (2014) used impact data to evaluate the performance of their flash-flood warnings. The IRIP method has also been evaluated by comparison with impact data on roads (Lagadec et al, 2016b) and on railways (Dehotin et al, 2015b;Lagadec et al, 2016a). During these evaluation tests, good probabilities of detection were obtained but also high false-alarm ratios because numerous areas where identified as susceptible to surface runoff but no impact has been recorded.…”
Section: Scientific Issuesmentioning
confidence: 99%
“…Defrance et al (2014) and Javelle et al (2014) used impact data to evaluate the performance of their flash-flood warnings. The IRIP method has also been evaluated by comparison with impact data on roads (Lagadec et al, 2016b) and on railways (Dehotin et al, 2015b;Lagadec et al, 2016a). During these evaluation tests, good probabilities of detection were obtained but also high false-alarm ratios because numerous areas where identified as susceptible to surface runoff but no impact has been recorded.…”
Section: Scientific Issuesmentioning
confidence: 99%
“…In other works, risk regulatory zonings of surface runoff and soil erosion as well as post-event survey data of impacts on infrastructures and transport networks such as roads and railways were used to evaluate the IRIP model on several case studies in France [23][24][25]. IRIP was also applied in the same context to other regions (near Antibes in [26] and the Bayonne area in [27]). Recently, Braud et al [6] suggested a robust and generic method to evaluate the IRIP susceptibility maps using runoff-related proxy data in the railway context.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in hydrology use proxy data to evaluate models, such as flooded road reports (Naulin et al, 2013;Versini et al, 2010aVersini et al, , 2010b, observations of gravitational hazards in mountainous areas (Defrance, 2014), and post-event surveys (Javelle et al, 2014;Ortega et al, 2009). Concerning the IRIP method evaluation, few comparisons have been performed with proxy data such as surface runoff impact locations on railways (Dehotin et al, 2015b) and natural disaster declaration locations from the Gaspar French database (Dehotin and Breil, 2011a). However, these tests have been performed for few case studies and remain qualitative.…”
Section: Introductionmentioning
confidence: 99%